Reintegration of Pakistani Return Migrants from the Middle East in the Domestic Labour Market (The Pakistan Development Review, 1998)
This study aims, first, to assess unemployment levels among both return migrants and non-migrants and, second, to examine the reintegration pattern of returnees in the domestic labour market. The study has used three data sets: the 1980 PIDE/World Bank Survey of Return Migrant Households, the 1986 ILO/ARTEP Survey of Return Migrant Households, and the 1991 Pakistan Integrated Household Survey. The results show that unemployment rates are much higher among return migrants than among non-migrants. Although this difference has narrowed with the passage of time, even among those who returned to Pakistan at least 18 months prior to the surveys, more than 10 percent of workers are unemployed. The multivariate analysis further shows that returnees, irrespective of the period elapsed since their return, are more likely to be unemployed than non-migrants. With respect to the reintegration pattern of return migrants, the study reveals that the variables indicating their human capital such as occupation and premigration and during-migration work experience appear to have greater influence on their re-absorption than the variables related to economic positions such as savings. The possibility is that unemployed returnees can not save enough from their overseas earnings to become self-employed. Provision of credit for self-employment seems to be the right way to accommodate these workers. The study also shows that the majority of workers who are able to find employment on return are satisfied with their post-return jobs and income levels, suggesting their successful reintegration in the domestic labour market.